Intraorbital Cavernous Haemangioma (CHM) (Journal of Armed Forces Medical College, Bangladesh, 2010)
This is an interesting and rare case report of right intraorbital cavernous haemangioma near optic nerve of a12 years boy who was hospitalized for right sided uniocular moderate axial proptosis and headache withoutany impairment of vision. Computed Tomographic (CT) scan showed fusiform enlargement of around rightoptic nerve just behind the eye ball. The mass was removed by right fronto-orbito-zygomatotomy incision anddiagnosed post-operatively as intraorbital cavernous haemangioma (CHM).Key words: Intraorbital cavernous haemangioma.DOI: 10.3329/jafmc.v6i1.5990Journal of Armed Forces Medical College, Bangladesh Vol.6(1) 2010 p.32-33